The effect of critical thinking on students' accounting competency in vocational high school - Risa Alkurnia; Susilaningsih Susilaningsih; Sudiyanto Sudiyanto (Jurnal Pendidikan Vokasi, 2019)
The purpose of this study was to analyze the differences in the effect of critical thinking skills on students' learning competency in accounting subjects at vocational high school in Surakarta. The indicators of critical thinking ability used in this study referred to the theory developed by Ennis, while the accounting competency indicators used referred to Bloom's taxonomy. This research was experimental quantitative research. The population in this study were all students of grade X accounting at SMK 1 Surakarta totaling 96 students. The sample of this study was class X AC (Accounting) 2 as the experimental class and X AC 3 as the control class. The sampling technique used in this study was Cluster Random sampling. The data analysis technique used in the study was Analysis of Variance (ANOVA), with pre-requisite tests that had to be done before, namely normality and homogeneity tests. This study concluded that there are differences in the influence of critical thinking skills on students' competency in accounting learning.